Mediating Role Competitive Advantage between Customer Relationship, Supply Chain Collaboration Value Innovation and Supply Chain Capability and Supply Chain Performance: Manufacturing Industry Supported Sustainable Mobility in Indonesia - Muhammad Ikhsan Setiawan; Ronny Durrotun Nasihien; Mohd Adib Bin Mohammad Razi (International Journal of Supply Chain Management, 2019)
The basic objective of this paper is to examine customer relationship, Supply chain collaboration value innovation and Supply chain capability on supply chain performance. Moreover, the mediating impact of competitive advantage is examined as well. The data is collected from respondents of manufacturing sector of Indonesia. the total 244 questionnaires for the analysis of this study. In this study we have used PLS-SEM for data examination and provision of support for the development of hypothesis. The findings of the study revealed Supply chain collaboration and Supply chain capability has significant impact on competitive advantage. Rest of the relations have proved to be significant. The findings of the study will contribute in the limited literature of the supply chain performance. Moreover, the policy makers of the manufacturing sectors of the Indonesia can get benefit from it.